(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
This article focuses on the peculiarities of reflecting the “history” concept in the novel by famous writer Grygoriy Huseynov “Return to Portland”. This work is related to non-fiction literature samples and represents a true image of the 60ies period in the 20ieth century. The writer’s mastership, the author’s style originality, openness, frankness and recreating the past cultural atmosphere contribute to the fact that the reader not only completely trusts the narrator, but also naturally coexists with the characters and time and space coordinates of the work. The novel “Return to Portland” is the anthem to human freedom that can be saved even in a totalitarian society, which was the Soviet Union.